The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/02770903.2012.757776
|View full text |Cite
|
Sign up to set email alerts
|

The Association of a Variant in the Cell Cycle Control GeneCCND1and Obesity on the Development of Asthma in the Swiss SAPALDIA Study

Abstract: OBJECTIVE: The molecular mechanisms underlying the association between obesity (BMI 30 kg/m(2)) and asthma are poorly understood. Since shifts in the fate of bronchial cells due to lowgrade systemic inflammation may provide a possible explanation, we investigated whether two of the best documented functional variants in cell cycle control genes modify the obesity-asthma association. METHODS: We genotyped 5930 SAPALDIA cohort participants for the single-nucleotide polymorphisms (SNPs) rs9344 in the cyclin D1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Further, Lim et al reported that the increased expression of obesity-associated molecules increases the risk of development of mammary gland tumors in obese female canines [51]. These pathways are enriched with numerous genes and in fact, the mutations in a few key genes have been described to affect obesity or blood sugar trait [12,49,[52][53][54]. In total, 64 genes were significantly enriched in cancer-related pathways and several significant genes such as cyclic AMP-responsive element-binding protein 5 (CREB5) [55], AKT serine/threonine kinase 3 (AKT3) [53], cyclin D1 (CCND1) [12,52], Wnt family member 1 (WNT1) [49,54] were identified to be associated with blood sugar and obesity traits.…”
Section: Cancer-related Pathwaysmentioning
confidence: 99%
“…Further, Lim et al reported that the increased expression of obesity-associated molecules increases the risk of development of mammary gland tumors in obese female canines [51]. These pathways are enriched with numerous genes and in fact, the mutations in a few key genes have been described to affect obesity or blood sugar trait [12,49,[52][53][54]. In total, 64 genes were significantly enriched in cancer-related pathways and several significant genes such as cyclic AMP-responsive element-binding protein 5 (CREB5) [55], AKT serine/threonine kinase 3 (AKT3) [53], cyclin D1 (CCND1) [12,52], Wnt family member 1 (WNT1) [49,54] were identified to be associated with blood sugar and obesity traits.…”
Section: Cancer-related Pathwaysmentioning
confidence: 99%
“…From the miRNA-hub gene network construction and TF-hub gene network diagram, it can be observed that UBE2D3, HSP90AA1, PAK2, DDB1, DVL3, FYN, ABL1, SMAD3, STAT3, PRKCA, EGFR, PSMC4, CCND1, FOXO1, hsa-mir-6127, hsa-let-7d-5p, hsa-mir-8063, hsa-mir-329-3p, hsa-mir-1207-5p, hsa-mir-4651, hsa-mir-410-5p, hsa-mir-222-3p, hsa-mir-29c-3p, hsa-mir-663a, E2F1, HCFC1, SRY, ZFX, RUNX1, SPI1, MYBL2, SUZ12, TBX3 and YAP1 were the key nodes of the miRNA-hub gene network construction and TF-hub gene network, with the highest node degree value. Expression of the CCND1 gene plays a role in the development of obesity [189], but this gene might be associated with progression of GDM. FOXO1 [190], hsa-mir-1207-5p [191], hsa-mir-4651 [191], hsa-mir-222-3p [192] and E2F1 [193] are essential for the progression of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Target genes -miRNA regulatory network up regulated genes was constructed and analyzed. CCND1 was responsible for progression of obesity [209]. CCND2 was associated with development of insulin resistance [210].…”
Section: Discussionmentioning
confidence: 99%